The influence of environmental variations on the phenolic compound profiles and antioxidant activity of two medicinal Patagonian valerians (Valeriana carnosa Sm. and V. clarionifolia Phil.) - Nagahama, Nicolas; Gastaldi, Bruno; Clifford, Michael; Manifesto, Maria Marcela; Fortunato, Renee Hersilia (AIMS Press, 2020)
Valeriana carnosa and V. clarionifolia stand out as principal elements in the indigenous pharmacopeias of Patagonia; however, their phytochemical characterization is unknown. This study constitutes the starting point of a general project that aims to characterize secondary metabolites in these species. The variability of phenolic compounds in root ethanolic extracts was analyzed and compared for thirteen populations of V. carnosa and two of V. clarionifolia from the south of Argentinean Patagonia. Phenolic content was quantified by the Folin-Ciocalteu method and the putative phenolic compound profiles were investigated using HPLC-UV-MS. Antioxidant activity was evaluated through 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assays. Total phenolic content values ranged from 5.6 to 16.6 mg GAE/g in V. carnosa and 7.3 to 9.7 mg GAE/g in V. clarionifolia. Antioxidant evaluation results evidenced that the percentage of neutralized DPPH varied between 26% and 85% in V. carnosa and 39% and 58% in V. clarionifolia. A positive correlation between total phenolic content and antioxidant activity (r = 0.90) was observed. In V. carnosa total phenolic content was not correlated with altitude or latitude (p > 0.05), and chemical variability seems to be associated with genetic variability and/or different growing habitats (microclimatic conditions). However, the presence of some specific phenolic compounds was associated with latitude. In V. carnosa and V. clarionifolia 15 and 10 phenolic compounds were tentatively identified, respectively, and several of these are reported to have beneficial attributes from a phytomedical viewpoint. This study contributes to the phytochemical characterization project of these two medicinal valerians from Patagonia.